The Big Five Cognitive and Neuropsychological Correlates: A Review in the Field of Neuroscience of Personality (2015)
Introduction: Neuroscience of personality is an area of study whose origins are relatively recent. Objective: The study of the neurobiological and neuropsychological fundamentals of personality. Methodology: This is a narrative review article that presents and discusses some, perhaps the majority, of the research in this field. The structure of the article is based on the five main personality factors. For each factor (neuroticism, extroversion, openness, friendliness and responsibility) the existing literature is reviewed and discussed in relation to the neuropsychological correlates in the executive function, memory and intelligence. Results: Because this is a recent field of study and due to the type of review carried out, it was not possible to reach a precise conclusion; in other words, in the current state-of-the-art, it cannot be determined how the factors and facets of personality correlate with the executive function, intelligence and memory. Conclusion: In general terms, it may be affirmed that there is a different neuropsychological profile for each factor.